Urodynamic Studies for the Diagnosis of Lower Urinary Tract Symptoms: Experience in BSMMU - Ullah, ATM Aman; Haque, Md Anamul; Alam, AKM Khurshidul; Islam, AKM Anwarul (Bangladesh Journal of Urology, 2020)
Objectives: The aim of urodynamic testing is to obtain objective information regarding urinary bladder storage and voiding function. This investigation provides information of the underlying causes depending on the individual situation and findings. Materials and Methods: This Retrospective study of the UDS was conducted at Urology department of Bangabandhu Sheikh Mujib Medical University, Dhaka from January 2012 to April 2017. A total of 403 cases of urodynamic studies done. Patient age range was 10-85 years. Female Patient was only 41 and post operative cases was only six. Bladder dairy, Ultrasonography of Kidney, ureter, bladder with maximum cystometric capacity (MCC)and post void residue (PVR), Urine culture were done for most of the patient. Patient with indwelling catheter was remove and clean intermittent catheterization was demonstrated. There was no patient with pace maker or valve replacement. We didn’t use routine prophylactic antibiotics, Patients was advice to contact to UDS room physically or over telephone if they feel fever, retention, and other complications. Urodynamic tests include uroflowmetry, postvoid residual measurement, cystometric test, leak point pressure measurement, pressure flow study, and few cases with electromyography. Results: Among them most cases are equivocal and obstructive cases are ranked second about 68 cases (16.87 These were Benign Prostatic Hyperplasia (BPH), stricture urethra, atonic bladder, and dysfunctional voiding. Only five patients had urinary tract infections (1.2%) with rise of temperature but only two had cultural positive and treated with sensitive antibiotics. Organism were streptococcus aureus and pseudomonus. One female and one male patient develop retention and relived by continuous catheterisation and after 7 days removed catheter. Conclusions: Urodynamics could help most diagnosis of LUTSs in most of the cases. We are not yet in using video urodynamics instead urethrocystoscopy may help in assessing the urethra and bladder neck. Bangladesh Journal of Urology, Vol. 21, No. 1, January 2018 p.8-13